The Effect of Perceived Value, Trust, and Commitment on Patient Loyalty in Taiwan - Ing-Chung Huang PhD; Pey-Lan Du PhD; Long-Sheng Lin PhD; Ting-Yu Liu MBA; Tsai-Fei Lin PhD Candidate; Wei-Chang Huang PhD Candidate (SAGE Publishing, 2021)
Increasing patient loyalty through improved health care quality and patient-provider relationships becomes the key factor in medical providers' successes. This study explored the mediated relationship of patients' perceived value, patient commitment, and patient loyalty and the moderating effect of patient trust on the mediated relationship. A cross-sectional research design was adopted. Mediation and moderated mediation were tested using the PROCESS macro v3.5 for the SPSS supplement. Convenience sampling was used for the distribution of questionnaires to members of the public with experience of seeking medical attention in Taiwan. Among the 254 valid questionnaires recovered, 59.4% of the respondents were male, 38.6% were married, 90.2% were in the 20 to 49 year age range, and 54.7% had a bachelor's degree or above. This study indicated a significant mediated relationship among patients' perceived value of medical services, commitment to the patient-provider relationship, and patient loyalty. Furthermore, when the patient demonstrated higher levels of trust in a healthcare provider, the relationship of perceived value, commitment, and patient loyalty was also enhanced. This study discussed and demonstrated the effect of perceived value, trust, and commitment on patient loyalty. The research suggests that improving patient loyalty benefits sustainable operation of medical providers and the treatment effects for patients.